Influence of external and internal factors on financial stability of an economic entity ("Journal "U". Economy. Management. Finance.", 2018)
The article analyses the notion of «financial stability» in the context of sustainable development of the economy as a whole and the economic entity in particular. The classification of external and internal factors that affect the stability of an economic entity is proposed.
Keywords: financial stability; sustainable development of the economic entity; external and internal factors of influence